Analisis Emotional branding Visualisasi Iklan Televisi Yamaha Fazzio Hybrid-Connected - Dian Eka Permanasari (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
This study analyzes emotional branding in the visualization of Yamaha Fazzio Hybrid-Connected television commercials. This study applies a qualitative-descriptive method with the approach of Marc Gobe's emotional branding theory. The results of the study show that visualization of Yamaha Fazzio Hybrid-Connected advertisements seeks to build emotional branding through a series of strategies such as building relationships with consumers, multi-sensory experiences, affirming vision, and imagination to establish communication with consumers as self-actualization.